Three-phase anaerobic digestion system for co-production of bio-hydrogen and bio-methane from food waste - Er, Aldred Guo Yao (2009)
The project was conducted to study leaching bed reactors for the hydrolysis of carbohydrate rich solid organic waste. It also explored the current leaching bed reactor designs and identified the best type of hydrolysis for the three-phase anaerobic digestion system (3PADS) for the co-production of hydrogen and methane. 2 types of hydrolysis such as hydrogenogenic hydrolysis and solubilisation hydrolysis were discussed and modelling calculations was conducted to assess the fed-batch leaching bed reactor performance of removing total volatile solids and starch. The appropriate type of seed sludge used and suitable operational design of the leaching bed for 3PADS was discussed. Hydrogenogenic hydrolysis produced leachates with high amount of soluble sugar and allowed for high rate of hydrogen gas production. Solubilisation hydrolysis allowed for high volatile solids degradation of solid organic waste. Batch experiments were conducted to understand such hydrolysis and it was found that pH adjustment and new substrate addition was needed after 4 days of experiment to allow for optimum hydrogenogenic hydrolysis. Metabolic shifts between acidogenesis and solventogenesis were influenced by changes in pH and it was identified that undissociated butyric acid initiated solventogenesis. Further batch experiments were conducted to determine the most appropriate seed sludge needed for hydrolysis and it was found that heated digested sludge was ideal for hydrolysis. A ratio of sludge-to-feedstock of 3 was also determined in the experiment for assessing the amount of seed sludge needed. Lastly, a fed batch experiment seeded with heated digested sludge was conducted where both optimum hydrogenogenic and solubilisation hydrolysis were achieved. Modelling calculations were also carried out where model calculations showed that 82.6% of total volatile solids were removed with 93% of the total starch degraded with the fed batch experiment.